Bright lights, big Christmas [compact disc, unabridged] - Andrews, Mary Kay, 1954- (Macmillan Audio, 2023)
Newly single and unemployed Kerry Tolliver needs a second chance. When she moves back home to her family's Christmas tree farm in North Carolina, she is guilt tripped into helping her brother, Murphy, sell trees in New York City. She begrudgingly agrees, but she isn't happy about sharing a trailer with her brother in the East Village for two months. Plus, it's been years, since before her parents' divorce, that she's been to the city to sell Christmas trees. Then, Kerry meets Patrick, the annoying Mercedes owner who parked in her spot for the first two days. Patrick is recently divorced, a father to a six year old son, and lives in the neighborhood. Can Kerry's first impressions about the recently divorced, single father, and--dare she say, handsome--neighbor be wrong? Surrounded by warm childhood memories, sparkling possibility, and the magic of Christmas in the City, will Kerry finally get the second chance she needs to find herself... and maybe even find love?